Case report: A novel third-generation anti-CD19/CD22 CAR T-cells combined with auto-HSCT for relapsed Burkitt lymphoma - Luo, Xiaodan; Chen, Ao; Qin, Le; Weinkove, Robert; Zhao, Rong; Ye, Ting; Chen, Sihui; Tang, Jianli; Liu, Jianbo; Huang, Jiayu; Shi, Boyun; Yuan, Danyun; et al. (Frontiers in Immunology, 2024)
This study explores a novel therapeutic strategy for relapsed/refractory (R/R) Burkitt lymphoma (BL) by integrating autologous hematopoietic stem cell transplantation (ASCT) with tandem anti-CD19/CD22 chimeric antigen receptor (CAR) T cell therapy. A 20-year-old Asian male with refractory BL, whose lymphoma had not responded to multiple chemoimmunotherapy regimens, received myeloablative ASCT followed three days later by infusion of a novel third-generation CAR T cells engineered with CD28 and CD3ζ signaling domains, along with a TLR2 costimulatory domain. This resulted in sustained complete remission at the 306-day follow-up, without experiencing any severe complications. This case suggests that combining myeloablative ASCT with tandem anti-CD19/CD22 CAR T cell therapy could be an effective approach for R/R BL, warranting further clinical validation.